2010
DOI: 10.1159/000321520
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implication of Plasma Osteopontin Levels in Patients with Chronic Kidney Disease

Abstract: Aims: To assess (a) plasma osteopontin (pOPN) in a cohort of chronic kidney disease (CKD) patients; (b) the relationship between pOPN and aortic calcification and stiffness, and (c) the association between pOPN and the overall and cardiovascular mortality risk. Methods: pOPN, the abdominal aortic calcification score and pulse wave velocity (PWV) were determined in 94 CKD patients (68 ± 13 years; 60% males; 31% at CKD stages 2–3, 31% at stages 4–5, 38% at stage 5D), prospectively followed for mortality. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 88 publications
(58 reference statements)
2
23
0
6
Order By: Relevance
“…These increased levels also correlated closely with serum phosphate and intact parathyroid hormone. Comparable findings by Barreto et al in CKD patients and Yamaguchi et al in diabetic patients with renal failure demonstrated increased serum OPN levels that associated with loss of renal function 54, 55 . It is likely that OPN levels increase to offset further pathologic renal calcification as OPN is upregulated at sites of pathologic calcification.…”
Section: Discussionmentioning
confidence: 68%
“…These increased levels also correlated closely with serum phosphate and intact parathyroid hormone. Comparable findings by Barreto et al in CKD patients and Yamaguchi et al in diabetic patients with renal failure demonstrated increased serum OPN levels that associated with loss of renal function 54, 55 . It is likely that OPN levels increase to offset further pathologic renal calcification as OPN is upregulated at sites of pathologic calcification.…”
Section: Discussionmentioning
confidence: 68%
“…In patients with chronic kidney disease elevated circulating OP level has been reported but except for a small group of HD patients no independent association could be detected between OP level and VC [46, 47]. In experimental uremia plasma OP was increased and correlated positively with aortic atherosclerosis [48].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in hemodialysis patients, OPN levels have been found to be significantly elevated as compared with control subjects, and to be positively correlated with the degree and severity of aortic calcification [113]. Elevated plasma OPN levels were found during the early stages of chronic kidney disease (CKD) [114]. However, no association was found between OPN and aortic calcification score [114].…”
Section: Osteopontin (Opn)mentioning
confidence: 99%
“…Elevated plasma OPN levels were found during the early stages of chronic kidney disease (CKD) [114]. However, no association was found between OPN and aortic calcification score [114]. The positive association between plasma OPN and clinical outcomes (such as overall and cardiovascular mortality) was also associated with inflammatory status [114].…”
Section: Osteopontin (Opn)mentioning
confidence: 99%